SHP2-Mediated Signal Networks in Stem Cell Homeostasis and Dysfunction - Chen Kan; Fan Yang; Siying Wang (Hindawi Limited, 2018)
Stem cells, including embryonic stem cells (ESCs) and adult stem cells, play a central role in mammal organism development and homeostasis. They have two unique properties: the capacity for self-renewal and the ability to differentiate into many specialized cell types. Src homology region 2- (SH2-) containing protein tyrosine phosphatase 2 (SHP-2), a nonreceptor protein tyrosine phosphatase encoded by protein tyrosine phosphatase nonreceptor type 11 gene (PTPN11), regulates multicellular differentiation, proliferation, and survival through numerous conserved signal pathways. Gain-of-function (GOF) or loss-of-function (LOF) SHP2 in various cells, especially for stem cells, disrupt organism self-balance and lead to a plethora of diseases, such as cancer, maldevelopment, and excessive hyperblastosis. However, the exact mechanisms of SHP2 dysfunction in stem cells remain unclear. In this review, we intended to raise the attention and clarify the framework of SHP2-mediated signal pathways in various stem cells. Establishment of integrated signal architecture, from ESCs to adult stem cells, will help us to understand the changes of dynamic, multilayered pathways in response to SHP2 dysfunction. Overall, better understanding the functions of SHP2 in stem cells provides a new avenue to treat SHP2-associated diseases.